AB0487 Etanercept increases step activity in patients with active rheumatoid arthritis and short disease duration. (23rd January 2014) - Willeke, P.; Winter, C.; Schotte, H.; Becker, H.; Marx, J.; Gaubitz, M.; Rosenbaum, D.
Abstract : Background: There is strong evidence that TNF-alpha inhibitors improve disability and activities of daily living in patients with active rheumatoid arthritis (RA). However, the supporting data have been generated mainly by the health-assessment-questionnaire (HAQ) that is based on subjective variables. It is desirable to add objective parameters reflecting patients' activities to the outcome parameters in RA. The StepWatch™ activity monitor (SAM) is an ankle worn step counter and an accurate instrument to measure real world activities of daily living. Objectives: Our purpose was to investigate whether step counts measured with the SAM increase during a therapy with the TNF-alpha inhibitor etanercept (ETN) in patients with active RA and further to correlate the data with the results of the HAQ and the DAS28 in these patients. Methods: We included 26 patients with active RA who started a therapy with ETN 50 mg subcutaneously/week. Before therapy, after 4 weeks, and after 12 weeks step activity was measured for a period of 7 days with the SAM. The results were also correlated to the HAQ and the DAS28. Results: 23 patients completed the study. A significant increase of the steps per hour was measured after 12 weeks in patients with shorter disease duration of RA (<5 years, n=10), (407 steps/h ± 161 vs. 512 steps/h ± 134, p≤0.02). The HAQ and the DAS28 improved significantly in this group after 12 weeks (HAQ: 1.49±0.82 at baseline vs. 0.85±0.71 after week 12, p<0.01 and DAS28: 5.21±0.72 vs. 3.2±0.68, p<0.01). In patients with longer disease duration (n=13) no significant increase of step activity was noted after 12 weeks (467 steps/h ± 178 vs. 407 steps/h ± 108, p=0.53) although also in this group a significant improvement of the HAQ or the DAS28 was noted (HAQ: 1.71±0.89 at baseline vs. 1.02±0.56 after week 12, p<0.01 and DAS28: 5.09±0.89 vs. 3.3±1.12, p<0.01). Conclusions: Measuring the step activity by SAM reveals an objective real life parameter of functional capacity of RA patients. If ETN is initiated in patients with shorter disease duration an increase of step activity could be achieved beside the developments in the DAS28 or the HAQ. However, the increase of step activity could not be achieved in patients with long standing disease duration. This emphasizes the need for an early effective therapy before RA activity leads to potentially irreversible destructions of the joints. Disclosure of Interest: P. Willeke Grant/Research support from: Pfizer Inc., C. Winter: None Declared, H. Schotte: None Declared, H. Becker: None Declared, J. Marx: None Declared, M. Gaubitz Grant/Research support from: Pfizer Inc., Abbott Immunology Pharmaceuticals, Roche Pharma, Consultant for: Pfizer Inc., D. Rosenbaum: None Declared